Patient participation during primary health‐care encounters among adult patients with multimorbidity: A cross‐sectional study - Leila Paukkonen; Anne Oikarinen; Outi Kähkönen; Helvi Kyngäs (Wiley, 2021)
Abstract Background Patient participation is essential for achieving high‐quality care and positive outcomes, especially among patients with multimorbidity, which is a major challenge for health care due to high prevalence, care complexity and impact on patients' lives. Objective To explore the patient participation related to their own care among patients with multimorbidity in primary health‐care settings. Methods A cross‐sectional survey was conducted among adult multimorbid patients who visited primary health‐care facilities. The key instrument used was the Participation in Rehabilitation Questionnaire. Data representing 125 patients were analysed using various statistical methods. Results The respondents generally felt patient participation to be important, yet provided highly varying accounts regarding the extent to which it was realized by professionals. Information and knowledge and Respect and encouragement were considered the most important and best implemented subcategories of participation. Several patient‐related factors had a statistically significant effect on patient perceptions of participation for all subcategories and as explanatory factors for perceptions of total participation in univariate models. Most patients reported active participation in health‐care communication, positively associated with patient activation and adherence. Gender, perceived health, patient activation and active participation were explanatory factors for total importance of participation in multivariate models, while patient activation was retained for realization of participation. Conclusions Multimorbid patients require individualized care that promotes participation and active communication; this approach may further improve patient activation and adherence. Poor perceived health and functional ability seemed to be related to worse perceptions of participation. Patient and public involvement The study topic importance was based on the patients' experiences in author's previous research and the need to develop patient‐centred care.